2009
DOI: 10.1002/app.30020
|View full text |Cite
|
Sign up to set email alerts
|

Graft copolymerization of maleic anhydride onto low‐molecular‐weight polyisobutylene through solvothermal method

Abstract: The free‐radical graft copolymerization of maleic anhydride (MAH) onto highly reactive low molecular weight polyisobutylene was conducted by the use of benzoyl peroxide as an initiator through the solvothermal method. Fourier transform infrared spectra and 1H‐NMR spectra confirmed that maleic anhydride was successfully grafted onto highly reactive low molecular weight polyisobutylene backbone, and the grafting mechanism also was proposed. The effect of benzoyl peroxide content, MAH concentration, total reactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…As reported in previous work, 23–25 extrusion of PP‐ g ‐MA typically results in partial hydrolysis due to ambient humidity and high heat, resulting in PP‐ g ‐SA (Figure 1).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…As reported in previous work, 23–25 extrusion of PP‐ g ‐MA typically results in partial hydrolysis due to ambient humidity and high heat, resulting in PP‐ g ‐SA (Figure 1).…”
Section: Resultssupporting
confidence: 69%
“…As a widely available commercial product, PP‐ g ‐MA has been used previously in the development of functional polymers as an intermediate to bind other antioxidant compounds such as green tea extract, 20 catechin, 21 and thymol essential oil 22 . However, it has also been reported that MA often undergoes partial hydrolysis during extrusion to form polypropylene‐ graft ‐succinic acid (PP‐ g ‐SA) 23–25 . PP‐ g ‐SA has a similar structure to other dicarboxylic acid compounds with antioxidant functionality such as ethylenediaminetetraacetic acid (EDTA), nitrilotriacetic acid (NTA), and iminodiacetic acid (IDA), but, to the best of the authors' knowledge, neither the dissociation behavior nor the radical scavenging capacity of PP‐ g ‐SA has been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEW‐ g ‐MAH was synthesized through solution approach with MAH as grafted monomer and BPO as an initiator, the schematic diagram of PEW‐ g ‐MAH is shown in Figure . First, PEW, MAH, and BPO were put into the three neck flask (250 mL) and dissolved in xylene after heating and stirring.…”
Section: Methodsmentioning
confidence: 99%
“…The solvothermal method is a general method for fabricating crystalline nanoparticles in the inorganic chemistry field, and the reaction temperature is often set to lower than 200°C; this also fits the reaction for polymers. Because of the increased solubility and reactivity of the compounds and complexes under high temperatures and pressures, the solvothermal method can be used to synthesize copolymers that are difficult to obtain by traditional methods . The organic functional groups under these circumstances are more reactive, and the polymerization process is easier to facilitate and more effective.…”
Section: Introductionmentioning
confidence: 99%